A matter of trust [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Montana rescue., 2017)
"Champion backcountry snowboarder Gage Watson left the limelight behind after being sued and remade his life as a ski patrol in Montana's rugged mountains and serving on the PEAK Rescue team. When a US Senator's brother goes missing, Gage is tasked for the rescue which becomes more complicated when the bossy, beautiful senator decides to join the search"--